recall that a polynomial can be written as the multiplication of multiple factors, namely of the form
![(x\text{ - c)}](https://img.qammunity.org/2023/formulas/mathematics/college/thb906l3vdkx9scyqktdi261vafrx9r07n.png)
where c is a zero of the function. Note that when having a complex zero, we must have the complex conjugate as another zero. Recall that given a complex number of the form a+bi, the complex conjugate is a-bi. Recall that
![(x+a)\cdot(x-a)=x^2-a^2](https://img.qammunity.org/2023/formulas/mathematics/college/6019urin1r9b8bdvk7rbz8xtf8edn6jpbu.png)
So will calculate the product of each pair of zeros:
![(x\text{ - 4i)}\cdot(x\text{ - (-4i)=(x-4i)}\cdot(x+4i)=x^2-(4i)^2=x^2-(4)^2(i)^2=x^2\text{ -16}\cdot(-1)=x^2+16](https://img.qammunity.org/2023/formulas/mathematics/college/qcr88sy8xqnqqgx9e7pjzk7m8emxgqelhy.png)
in the same manner, we would have
![(x\text{ -(2-i))}\cdot(x\text{ -(2+i))=((x -2)+i)}\cdot((x-2)-i)=((x-2)^2-i^2)=((x-2)^2\text{ +1)}](https://img.qammunity.org/2023/formulas/mathematics/college/kv0ra30avdbyeeojrnzv6sesvktlb8bxf2.png)
so we have that our polynomial would be
![(x\text{ -4i)}\cdot(x+4i)\cdot(x\text{ -(2+i))}\cdot(x-(2-i))=(x^2+16)\cdot((x-2)^2+1))](https://img.qammunity.org/2023/formulas/mathematics/college/trkou5gmxsnl2qlws6i4juxcup40gigpw1.png)
Now we only need to calculate the product of the right. So we have
![(x^2+16)\cdot((x-2)^2+1)=(x^2+16)\cdot(x^2-4x+4+1)=(x^2+16)\cdot(x^2\text{ -4x +5)}](https://img.qammunity.org/2023/formulas/mathematics/college/5wr0f4oynrwfih127ctuvs45zi4droazz4.png)
now we distribute to get
![(x^2+16)\cdot(x^2-4x+5)=x^2\cdot x^2\text{ -4x}\cdot x^2+5x^2+16x^2\text{ -16}\cdot4x+16\cdot5=x^4-4x^3+21x^2\text{ -64x}+80](https://img.qammunity.org/2023/formulas/mathematics/college/pnbq24hsupv050rzyv6oelglmidim9s534.png)
which would be our final answer